Experimental studies to study the efficacy of "Tarzan, VE" against Blattoptera representatives - R. M. Akbaev; L. V. Nacheva; A. A. Generalov (Российский паразитологический журнал, 2021)
The purpose of the research is studying the efficacy of "Tarzan, VE" against representatives of the Blattoptera order, Blattella germanica.Materials and methods. Experimental studies to study the efficacy of "Tarzan, VE" on representatives of the Blattoptera order were performed for two weeks at the premises of the Skryabin MVA (Moscow) and the KemSMU (Kemerovo). The study object was the red German cockroach B. germanica, a laboratory culture of which was grown in the MVA insectarium. Experiments 1 and 2 consisted of three tests of three sets each: a test to study the efficacy of the drug against cockroaches by the topical application; and a test to study the efficacy of "Tarzan, VE" against cockroaches by the forced exposure of arthropods to test surfaces, namely, plywood or glass previously treated with the drug in different concentrations. Dead insects were counted after a day.Results and discussion. We established the efficacy of "Tarzan, VE" in the form of an active substance in different dilutions against cockroaches B. germanica of both sexes using the topical application. Its efficiency decreases to 97% when diluted 1000 times (0.001N). With forced exposure to treated test surface (plywood), the efficacy of “Tarzan, VE” depended on the substance diluted: 90% at 0.01N, 83.3% at 0.005N, and 50% at 0.001N. The maximum effect of "Tarzan, VE" was observed when using the method of forced exposure of cockroaches to the treated test surface, glass. The efficacy of the drug in this case was 100% regardless of the sex and development stage of cockroaches. It was found that different concentrations of the insecticide had a toxic effect on the imago of both sexes and larval stages of cockroach development. The insecticidal nature of the drug is ensured by the use of zeta-cypermethrin as an active ingredient. "Tarzan, VE" insecticide can be recommended to control and prevent the distribution of B. germanica.